Numerical Assessments of Excess Ice Impacts on Permafrost and Greenhouse Gases in a Siberian Tundra Site Under a Warming Climate - Park, Hotaek; Fedorov, Alexander N.; Konstantinov, Pavel; Hiyama, Tetsuya (Frontiers in Earth Science, 2021)
Excess ice that exists in forms such as ice lenses and wedges in permafrost soils is vulnerable to climate warming. Here, we incorporated a simple representation of excess ice in a coupled hydrological and biogeochemical model (CHANGE) to assess how excess ice affects permafrost thaw and associated hydrologic responses, and possible impacts on carbon dioxide and methane (CH4) fluxes. The model was used to simulate a moss-covered tundra site in northeastern Siberia with various vertical initializations of excess ice under a future warming climate scenario. Simulations revealed that the warming climate induced deepening of the active layer thickness (ALT) and higher vegetation productivity and heterotrophic respiration from permafrost soil. Meanwhile, excess ice temporarily constrained ALT deepening and thermally stabilized permafrost because of the highest latent heat effect obtained under these conditions. These effects were large under conditions of high excess ice content distributed in deeper soil layers, especially when covered by moss and thinner snow. Once ALT reached to the layer of excess ice, it was abruptly melted, leading to ground surface subsidence over 15–20 years. The excess ice meltwater caused deeper soil to wet and contributed to talik formation. The anaerobic wet condition was effective to high CH4 emissions. However, as the excess ice meltwater was connected to the subsurface flow, the resultant lower water table limited the CH4 efflux. These results provide insights for interactions between warming climate, permafrost excess ice, and carbon and CH4 fluxes in well-drained conditions.